Exposure to nanographene oxide induces gene expression dysregulation in normal human astrocytes - Rudnytska Olha V.; Kulish Yuliia V.; Khita Olena O.; Minchenko Dmytro O.; Tsymbal Dariia O.; Viletska Yuliia M.; Sliusar Myroslava Y.; Trufanova Dariia D.; Minchenko Oleksandr H. (Endocrine Regulations, 2022)
Objective. Nanographene oxide, an oxidation derivative of graphene, is considered to be one of the nanomaterials attractive for biomedical applications, although this nanomaterial is toxic. The increasing exploitation of graphene-based materials necessitates a comprehensive evaluation of the potential impact of these materials on the human health. Moreover, it is necessary to investigate in detail the mechanisms of its toxic effect on living cells particularly at the genome level. The present study aimed to evaluate the impact of low doses of nanographene oxide on the expression of key regulatory genes in normal human astrocytes.